Class pet mess! - Gutman, Dan; Paillot, Jim (New York, NY Harper, an imprint of HarperCollinsPublishers, 2017)
Alexia is delighted when Mr. Cooper brings in Bob, a hognose snake, as class pet, but when Bob keels over, is Andrea's toy poodle or Alexia's neglect to blame?
English stories
Guided reading level K
Ages 4-8
2 23
Keywords: JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Readers / Beginner; JUVENILE FICTION / School & Education; Hognose snakes -- Fiction; Humorous stories; Pets -- Fiction; Schools -- Fiction; Snakes as pets -- Fiction